2020
DOI: 10.5115/acb.20.094
|View full text |Cite
|
Sign up to set email alerts
|

The estimation of age from elastic fibers in the tunica media of the aortic wall in a thai population: a preliminary study using aorta image analysis

Abstract: Image analysis has an increasing role in the identification of individuals in forensic application. Beside the bones, microstructural of arteries can be used in age estimation study. Aorta is the largest elastic artery which consists of many elastic fibers. Elastin in arterial wall highly resist to chemical and physical influence. The purposes of the study were to quantify elastic fibers in tunica media in each location of the aorta and examine the correlation between elastic fibers and age by using image anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Age-related changes in vascular diameter size were identified. Different changes occurred in the composition of each tunica layer within the artery walls, such as the irregular shape of endothelial cell, increasing of collagen fibers, and fewer smooth muscle cells [ 29 ]. Additionally, it was found that the elastic fibers diminished and began to fragment, particularly in the aorta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age-related changes in vascular diameter size were identified. Different changes occurred in the composition of each tunica layer within the artery walls, such as the irregular shape of endothelial cell, increasing of collagen fibers, and fewer smooth muscle cells [ 29 ]. Additionally, it was found that the elastic fibers diminished and began to fragment, particularly in the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Regular aerobic exercise can reduce aortic stiffness, regardless of its length or intensity. This complex effect is a result of various physiological responses to exercise, including elevated blood pressure and cardiac output, decreased peripheral resistance and smooth muscle tone with vasodilation, and elevated arterial compliance in the muscular arteries [ 29 ]. According to several earlier studies, physical activity under acute settings boosts blood flow and shear stress, which causes an increase in endothelial nitric oxide release [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was justified by Zarkovic et al [ 24 ] who stated that the structure of the aortic wall was altered in an age-related manner with a significant decrease of SMCs and elastic fibers accompanied by increased interlamellar space due to excessive formation of connective tissue between the elastic laminae. Komutrattananont et al [ 25 ] recorded that the mean percentage density of elastic fibers decreased in aortic wall with ageing and abdominal aorta showed the highest correlation with age followed by the thoracic aorta, the aortic arch, and the ascending aorta, respectively. They stated that these changes in the percentage density of elastic fibers can add information to age estimation purposes in human.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, collagen fibers are responsible for maintaining the structural integrity of the vessel wall and resistance to stretching. Replacement elastin fibers by SMCs and inelastic collagen fibers weaken the arterial walls and promote an aneurysm-like structure [ 22 , 23 , 24 , 25 , 26 ].…”
Section: The Biology Of Aortic Aneurysmsmentioning
confidence: 99%